PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP PRESTASI KERJA KARYAWAN UNIVERSITAS LANCANG KUNING PEKANBARU - Musfawati, Musfawati (Jurnal Niara, 2019)
This study aims to analyze and examine the influence of leadership and motivation of the university employee work preformance Lancang Kuning Pekanbaru. Research Methodology used is descriptive quantitative, while the population in this study are university employees who Lancang Kuning numbered 70 people. The Sampling Technique Is Stratifed Proportional Random Sampling. To determine the relationship and the influence of an independent variable to the model variables are bound to use Multiple Linear Regression Analysis. While to test the hypothesis using statistical tests. Research results show that the calculation statistically obtained Multiple Correlation Coefficient (r) with p value>0,05. Coefficient Of Determination (R2) OF 0,825 means that about 82,5% of leadership and motivational factors influencing job performance of employees Pekanbaru Universitas Lancang Kuning. Significant influence of leadership and motivational factors work against a university employee’s work performance Pekanbaru Lancang Kuning Presumptuous. Shown from Fhitung greater than the level Ftabel α = 5%. Of the research results show that FCountdown = 0,0000 and 6,992 > tCountdown = 1.660. These results show that leadership factors have a relationship and the most dominant influence on employee perfomance Lancang Kuning Pekanbaru University